Partial Purification and Some Properties of the Staphylococcus aureus Cytoplasmic Nitrate Reductase - Burke, Kathleen A. (1979)
The cytoplasmic nitrate reductase in heme mutant H-14 of Staphylococcus aureus was partially purified by steps which included ammonium sulfate fractionation and chromatography on Bio-Gel A 1.5m and ion-exchange columns. The active fractions from the ion-exchange columns showed two forms of the enzyme upon electrophoresis in nondenaturing gels of polyacrylamide; these corresponded to proteins of R(f) 0.16 and 0.28. Each form contained a predominant polypeptide of molecular weight 140,000, as shown by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The R(f) 0.16 form contained another major polypeptide of molecular weight 57,000, but the R(f) 0.28 form contained several other polypeptides. The sedimentation properties of the enzyme were examined after partial purification on Bio-Gel A 1.5m. In sucrose gradients containing Triton X-100 the enzyme sedimented as a homogeneous peak with an estimated molecular weight of 225,000; without detergent a heterogeneous profile was observed of molecular weight greater than 250,000. Treatment of the enzyme with trypsin increased the specific activity, and the enzyme sedimented as a homogeneous peak in sucrose gradients without Triton X-100, with an estimated molecular weight of 202,000. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis indicated that trypsin treatment converted the polypeptide of molecular weight 140,000 to a polypeptide of molecular weight 112,000. We conclude that the cytoplasmic nitrate reductase of S. aureus has a large subunit of molecular weight 140,000, which can be modified by trypsin to a polypeptide of molecular weight 112,000 without loss of catalytic activity.